Knowledge, knowledge cycle and art teaching in Brazil (Revista Educação, Artes e Inclusão, 2022)
Knowledge is present in the most varied areas related to the learning of individuals, including Art. For its consolidation, knowledge goes through a knowledge management cycle, which can be related to the perspective of Ana Mae Barbosa's Triangular Approach. Understanding the path that knowledge takes in the process of teaching Art, allows us to articulate Art and knowledge through the cycle of knowledge management. Therefore, this article seeks to understand how the knowledge management cycle manifests itself in the teaching of Art from the perspective of Ana Mae Barbosa's Triangular Approach. Thus, this research aims to understand the theoretical imbrication between Ana Mae Barbosa's Triangular Approach and Kimiz Dalkir's knowledge cycle in the context of Art teaching in Brazil. For this, a narrative literature review was carried out based on publications by Ana Mae and Dalkir, in addition to those with adherence to the topic addressed. The result of this research shows that there is a joint articulation between the Triangular Approach and Dalkir's knowledge cycle. It is evident that in Art education based on the Triangular Approach, the knowledge management process occurs.
Keywords: Teaching; Art; Knowledge management; Knowledge cycle